2014
DOI: 10.5603/ep.2014.0029
|View full text |Cite
|
Sign up to set email alerts
|

Charakter wzrostu gruczolaków przysadki typu prolactinoma zależy od stężenia prolaktyny i płci pacjentów, ale nie od wartości wskaźnika Ki-67

Abstract: Introduction: The objective of this study was to investigate the effects of some clinical and pathological features of prolactinomas on tumour behaviour. Material and methods:The study included 113 patients with prolactinoma (27 male, 86 female), with a mean age at diagnosis of 34.4 ± ± 10.0 years (40.3 ± 12.6 in males, 32.6 ± 8.3 in females). Patients were grouped as invasive or non-invasive according to radiological imaging findings. Ki-67 levels were evaluated if possible. Results: The mean adenoma size (lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…Similar to other investigators, we showed that preoperative serum prolactin concentrations correlated positively with prolactinoma size (15,31), tumor invasiveness (15,32), and patient age (33). The positive relationship between age and prolactin concentrations may be explained by larger tumors observed in older patients than in younger individuals (33).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to other investigators, we showed that preoperative serum prolactin concentrations correlated positively with prolactinoma size (15,31), tumor invasiveness (15,32), and patient age (33). The positive relationship between age and prolactin concentrations may be explained by larger tumors observed in older patients than in younger individuals (33).…”
Section: Discussionsupporting
confidence: 89%
“…In another study, invasive and noninvasive prolactinomas, as assessed radiologically, also had similar Ki-67 indices (15). Thus, radiological and microscopic markers of prolactinoma invasiveness seem unrelated.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Obviously, correct assessment of tumor invasion is mandatory for this approach, as is evaluation of proliferation. Indeed, in our review of the literature we found a robust association between proliferation, assayed by Ki-67, and presence of invasiveness with 62% of revised reports suggesting a positive correlation [145][146][147] and 38% indicating an unclear association, albeit with a positive trend [13,148,149]. The controversial data on p53 and Ki-67 expression and correlation with invasiveness might in part be a result of differences in defining invasion, as reported by Sarkar et al [140] and discussed herein.…”
Section: Pathological and Molecular Considerationsmentioning
confidence: 86%
“…The reported frequency of invasive PAs varies considerably, from 2-3% [8] to 21% [9,10]. Predilected sex remains matter of debate, although they seem to be larger and more frequent in men [11][12][13][14]; conflicting results are reported for age incidence [15], including those in childhood and adolescence [16][17][18][19][20].…”
Section: Epidemiologymentioning
confidence: 99%